Knowledge, attitude and practice among midwives and community nurses on cervical cancer in the state of Kedah in 1997 - Aishah Ahmad Makinuddin,; Osman Ali, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross sectional study was conducted on the knowledge, attitude and practice among midwives and community nurses on cervical cancer in the health service in the state of Kedah in January 1997. A universal sampling method was used and a total of 281 of people responded to the study. Data was collected by using self administered questionaires. The result of this study showed that a satisfactory dissemination of infon11ation on cervical cancer acquired from radio, tv , newspaper and staff nurses were associated with high level of knowledge on cervical cancer. A clear job description in cervical cancer prevention programmes and the age of respondents were associated with good attitude towards the programmes. There were 208 respondents (74.0010) who had Pap smear done. Among the reasons for not doing Pap smear were not married (25.8%), embarrassed (25.8%), did not have any symptoms (19.4%) and worried about the possible Pap smear result (14.5%). Those who were married, 79.0% of them had Pap smear done. There was a weak (r =0.250) but significant correlation between the score of knowledge and attitude towards cervical cancer preventive programmes (p<0.001). Duration of working with the Ministry of Health and satisfactory dissemination of information acquired from staff nurses were the predicting factor for carrying out Pap r\ smear. In conclusion, the above findings may be useful to increased the level of ~ knowledge and to change attitude and practice towards cervical cancer prevention programmes among midwives and community nurses in the state of Kedah.